Enhance Teaching using Google Classroom as a Digital Tool - Prasanna Dahal; Lubna Zaghlool (International Journal of Advanced Science and Computer Applications, 2025)
Google Classroom is gaining popularity as an online Learning Management System (LMS) and with the suite of free tools that comes with Google for Education, it is worthwhile knowing about.[1] Google Classroom is a fantastic platform to use because it works really well alongside the other apps in Google Suite for Education such as Gmail, Google Calendar, Google Docs, Google Slides, and Google Meet. The ease of having all these handy tools in one place helps to keep things as simple as possible when teaching online. Google Classroom can be used for most parts of delivering a lesson, from setting tasks, adding files, and marking student assignments [2] In this work we explain how to Create Google classroom, invite students to the class, add assignments and materials, Grade the assignments and leave feedback. The aim of the work is to enable teachers to create an online classroom area in which they can manage all the documents that their students need. Teachers can make assignments from within the class, which their students complete and turn in to be graded